Differential expression of two glial glutamate transporters in the rat brain: quantitative and immunocytochemical observations - Lehre, KP (J Neurosci, 1995)
Glutamate, the major excitatory neurotransmitter in brain, is almost exclusively intracellular due to the action of the glutamate transporters in the plasma membranes. To study the localization and properties of these proteins, we have raised antibodies specifically recognizing parts of the sequences of two cloned rat glutamate transporters, GLT-1 (Pines et al., 1992) and GLAST (Storck et al., 1992). On immunoblots the antibodies against GLT-1 label a broad heterogeneous band with maximum density at around 73 kDa, while the antibody against GLAST labels a similarly broad band at around 66 kDa in the cerebellum and a few kilodaltons lower in other brain regions. GLT-1 is expressed at the highest concentrations in the hippocampus, lateral septum, cerebral cortex, and striatum, while GLAST is preferentially expressed in the molecular layer of the cerebellum. However, both transporters are present throughout the brain, and have roughly parallel distributions in the cerebral hemispheres and brainstem. Preembedding light and electron microscopical immunocytochemistry shows that both GLT-1 and GLAST are restricted to astrocytes, which appear to express both proteins concomitantly, but in different proportions in different parts of the brain. Nerve terminal labeling was not observed. Both the amino and carboxyl terminals of GLT- 1 and GLAST are located intracellularly, indicating an even number of transmembrane segments. Antibodies against a synthetic peptide corresponding to amino acid residues 2–11 of the proposed sequence of GLT-1 recognize the native rat brain GLT-1 protein, confirming that the translation initiation site is at the first ATG.